In praise of commercial culture - Cowen, Tyler (W.E.B. Du Bois lectures., 1998)
Cowen's philosophy of cultural optimism stands in opposition to the many varieties of cultural pessimism found among conservatives, neo-conservatives, the Frankfurt School, and some versions of the political correctness and multiculturalist movements, as well as historical figures, including Rousseau and Plato. He shows that even when contemporary culture is thriving, it appears degenerate, as evidenced by the widespread acceptance of pessimism. He ends by considering the reasons why cultural pessimism has such a powerful hold on intellectuals and opinion-makers.